Spatiotemporal Control Over Multicellular Migration Using Green Light Reversible Cell–Cell Interactions. Issue 5 (14th January 2021) - Nzigou Mombo, Brice; Bijonowski, Brent M.; Rasoulinejad, Samaneh; Mueller, Marc; Wegner, Seraphine V.
Abstract: The regulation of cell–cell adhesions in space and time plays a crucial role in cell biology, especially in the coordination of multicellular behavior. Therefore, tools that allow for the modulation of cell–cell interactions with high precision are of great interest to a better understanding of their roles and building tissue‐like structures. Herein, the green light‐responsive protein CarH is expressed at the plasma membrane of cells as an artificial cell adhesion receptor, so that upon addition of its cofactor vitamin B12 specific cell–cell interactions form and lead to cell clustering in a concentration‐dependent manner. Upon green light illumination, the CarH based cell–cell interactions disassemble and allow for their reversion with high spatiotemporal control. Moreover, these artificial cell–cell interactions impact cell migration, as observed in a wound‐healing assay. When the cells interact with each other in the presence of vitamin B12 in the dark, the cells form on a solid front and migrate collectively; however, under green light illumination, individual cells migrate randomly out of the monolayer. Overall, the possibility of precisely controlling cell–cell interactions and regulating multicellular behavior is a potential pathway to gaining more insight into cell–cell interactions in biological processes. Abstract : Artificial cell–cell interactions based on the green light‐responsive protein CarH specifically form in the presence of its cofactor vitamin B12 and reverse upon green light illumination with high spatiotemporal precision. These interactions between the cells impact multicellular behavior such as the aggregation of cells and collective cell migration.